Phenobarbital and Valproate for Febrile Convulsions - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Data from 6 British trials of phenobarbital and 4 trials of valproate for the prophylactic treatment of febrile convulsions were polled and analyzed on an intention to treat basis at the Dept of Neurology, Royal Manchester and Booth Hall Children's Hospitals, Manchester.